Dipole tilt angle effect on magnetic reconnection locations on the magnetopause. Issue 7 (2nd July 2015) - Zhu, C. B.; Zhang, H.; Ge, Y. S.; Pu, Z. Y.; Liu, W. L.; Wan, W. X.; Liu, L. B.; Chen, Y. D.; Le, H. J.; Wang, Y. F.
Abstract: Plasma energy dispersion properties inside reconnection jet flows observed inside the low‐latitude boundary layer are used to determine the distances of observing satellites to reconnection sites. The locations of the reconnection sites are then retrieved by tracing the modeled field lines by those distances. The controlling effects of the dipole tilt angle to the location of X lines or reconnection sites are investigated. Our results show that the Earth's dipole tilt angles strongly modify the location of X lines predicted by Cooling et al's model, which is thought to be the result of magnetopause reshaping due to finite dipole tilt angles. Key Points: Particle energy dispersion is used to determine reconnection sites X line locations are controlled by the dipole tilt angle The locations of reconnection sites are retrieved by tracing modeled field lines